Household chores and household choices : theorizing the domestic sphere in historical archaeology - Barile, Kerri S.; Brandon, Jamie C. (Tuscaloosa, Ala. : University of Alabama Press, 2004)
The time is ripe for such an effort, as the questions that gather under the labels of modernity, the postmodern, and critical theory now transcend a single discipline. The work of John Rawls on justice in public life has had a generation of influence on scholarship, and this work seems to have a high degree of likelihood of making meaningful statements on these questions in the field.
Household chores; or the chore of defining the household / Jamie C. Brandon and Kerri S. Barile -- Analysis of household and family at a Spanish colonial rancho along the Rio Grande / Mindy Bonine -- A space of our own: redefining the enslaved household at Andrew Jackson's hermitage plantation / Whitney Battle -- Separate kitchens and intimate archaeology: constructing urban slavery on the antebellum cotton frontier in Washington, Arkansas / Leslie C. Stewart-Arbernathy -- "Living symbols of their lifelong struggles": in search of the home and household in the heart of Freedman's Town, Dallas, Texas / James M. Davidson -- Finding the space between spatial boundaries and social dynamics: the archeology of nested households / Nesta Anderson -- Hegemony within the household: the perspective from a South Carolina plantation / Kerri S. Barile -- A historic pay-for-housework community household: the Cambridge Cooperative Housekeeping Society / Suzanne Spencer-Wood -- Fictive kin in the mountains: the paternalistic metaphor and households in a California logging camp / Efstathios I. Pappas -- The ethnohistory and archaeology of Nuevo Santander Rancho households / Mary Jo Galindo -- Reconstructing domesticity and segregating households: the intersections of gender and race in the postbellum south / Jamie C. Brandon -- Working-class households as sites of social change / Margaret C. Wood -- What difference does feminist theory make in researching households? A commentary / Suzanne Spencer-Wood -- Doing the housework: new approaches to the archaeology of households / Mary C. Beaudry.
Includes bibliographical references (pages 263-305) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Historic sites -- United States; Material culture -- United States; Landscapes -- Social aspects -- United States -- History; Households -- United States -- History; Families -- United States; Sex role -- United States -- History; Archaeology and history -- United States; Feminist archaeology -- United States; Archaeology -- Methodology; United States -- Antiquities; Culture matérielle -- États-Unis.; Paysages -- Aspect social -- États-Unis -- Histoire; Ménages (Statistique) -- États-Unis -- Histoire; Familles -- États-Unis.; Rôle selon le sexe -- États-Unis -- Histoire; Archéologie et histoire -- États-Unis.; Féminisme et archéologie -- États-Unis.; Archéologie -- Méthodologie.; États-Unis -- Antiquités.; HOUSE & HOME -- Reference; FAMILY & RELATIONSHIPS -- General; Antiquities; Archaeology and history; Archaeology -- Methodology; Families; Feminist archaeology; Historic sites; Households; Landscapes -- Social aspects; Material culture; Sex role; United States; Haushalt; Archäologie; Ausgrabung; Geschichte; Lebensbedingungen; Siedlung; USA; History